A double-bond-rich nanofiber gel prepared by chemical vapor deposition, and its preparation method and application

The aqueous nanofibers are modified by chemical vapor deposition using double bond-containing acid chloride compounds, which solves the problem of poor reactivity of acid chloride compounds in the prior art in aqueous media, and realizes the preparation of double bond-rich nanofiber gels, improves its mechanical properties and functionality, and expands its application range.

CN115304789BActive Publication Date: 2025-03-07NANJING FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210946710.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-11
Publication Date
2025-03-07
Estimated Expiration
2042-08-11

AI Technical Summary

Technical Problem

When chemically modifying aqueous nanofibers with acid chloride compounds, the prior art encounters problems of poor reactivity and low stability, which leads to insufficient reactivity in aqueous media and makes it difficult to effectively modify nanofiber gels.

Method used

The aqueous nanofiber dispersion is subjected to double bond modification treatment by using the hydrolysis reaction of the double bond-containing acid chloride compound to form a double bond-rich nanofiber hydrogel or aerogel.

Benefits of technology

The physical aggregation and surface esterification modification of nanofibers have been achieved, the mechanical properties and functionality of the gel have been improved, and its applications in the fields of sustained release, filtration, catalysis, heat insulation, adsorption or sensors have been broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115304789B_ABST
    Figure CN115304789B_ABST
Patent Text Reader

Abstract

The present invention discloses a nanofiber gel rich in double bonds prepared by chemical vapor deposition, and a preparation method and application thereof. The preparation method comprises the following steps: by chemical vapor deposition, a double bond modification treatment is directly performed on an aqueous nanofiber dispersion using a reagent containing a volatile double bond compound to obtain a nanofiber hydrogel rich in double bonds; the volatile double bond compound is an acyl chloride compound containing double bonds. The nanofiber hydrogel rich in double bonds is freeze-dried to obtain a nanofiber aerogel rich in double bonds. The present invention can realize the one-step preparation of a functionalized hydrogel rich in double bonds from an aqueous nanofiber dispersion, which is simple to operate, green and environmentally friendly, and can be mass-produced. A large amount of double bond compounds are loaded inside the nanofiber hydrogel, and the surface of the nanofiber also has chemically bonded double bonds, which facilitates subsequent functionalization and is widely used in the fields of environmental protection and medicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gel preparation and production, and in particular to a nanofiber gel rich in double bonds prepared by a chemical vapor deposition method, and a preparation method and application thereof. Background Art

[0002] Biomass cellulose, chitin and silk have the characteristics of wide sources, renewable, easy to degrade and green and pollution-free. They have strong advantages in biological functional materials and have become a research hotspot for functional materials. Hydrogel or aerogel materials have a stable cross-linked three-dimensional network structure and have been widely used in tissue engineering, wound dressings, drug carriers or adsorbents, thermal insulation materials and other fields. Cellulose, chitin and silk are all nano-processed to obtain aqueous nanofiber dispersions. The nanofibers have unique physical and chemical properties such as high aspect ratio and high specific surface area, and have broad application prospects in the field of new functional materials.

[0003] Nanofiber gel materials can be divided into physical gel and chemical gel according to the forming mechanism. Chemical gel usually forms a stable network structure through covalent bonds by free radical polymerization, enzyme-catalyzed crosslinking, photocrosslinking, etc. with the assistance of a crosslinking agent. Physical gel mainly forms a three-dimensional network structure by entanglement between nanofiber aggregates through non-covalent bonds such as hydrogen bonds, electrostatic effects, and hydrophobic effects, and multiple effects jointly maintain the balance of the non-covalent system. Generally speaking, the preparation process of physical gel is simpler and easier to implement than chemical gel, and it is green and environmentally friendly, but its functional application is insufficient, and specific chemical modifications are required in the later stage to enhance its application performance. For example, Chinese patent CN106893116A discloses a method for preparing gel by reducing the electrostatic repulsion of nanofibers through an acid vapor bath to form physical crosslinking. This method uses a volatile solvent to prepare gel without direct contact with the dispersion liquid, which has the advantages of low cost and simple operation. However, there are still shortcomings in the mechanical properties of the prepared gel and the single surface chemical properties, and the application of the gel is greatly limited.

[0004] Chemical vapor deposition is an important method for functional modification of nanofiber aerogel materials. Matthieu et al. used palmitoyl chloride chemical vapor deposition to perform gas phase esterification modification on cellulose aerogels, and obtained a series of hydrophobic palmitic acid cellulose aerogels with different substitution degrees (Biomacromolecules, 2013, 14 (9): 3246-55.). However, the pressure (5-500 mbar) and temperature (100-200°C) must be strictly controlled during the reaction, and exhaust gas must be regularly vented to remove the hydrogen chloride byproduct produced by the esterification modification of the acyl chloride. Since acyl chloride compounds undergo hydrolysis reactions in water to produce organic acids and hydrochloric acid containing double bonds, resulting in poor reactivity and low stability in aqueous media, there are currently no reports on the direct use of acyl chloride compounds to chemically modify aqueous nanofibers and their hydrogels.

[0005] The present invention innovatively utilizes the double-bond-containing organic acid and hydrochloric acid produced by the hydrolysis reaction of the double-bond-containing acyl chloride compound. On the one hand, the hydrochloric acid produced can reduce the electrostatic repulsion of the nanofibers, causing the nanofibers to aggregate from the aqueous phase, thereby forming a physical cross-linked network to prepare a hydrogel; at the same time, the aggregation of the nanofibers increases the concentration of the nanofibers, which is more conducive to the esterification reaction between the double-bond acyl chloride compound and the surface hydroxyl group of the nanofibers to introduce covalently connected double bonds. On the other hand, the produced double-bond-containing organic acid can also reduce the electrostatic force between the nanofibers, causing the nanofibers to aggregate and overlap from the aqueous phase to form a hydrogel with better performance; at the same time, the organic acid can also be retained in the above-mentioned hydrogel, giving the hydrogel new double-bond functionality. In summary, the present invention uses a chemical vapor deposition method to directly perform double-bond modification treatment on the aqueous nanofiber dispersion using a reagent containing a volatile double-bond compound and obtains a functional nanofiber hydrogel rich in double bonds. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a nanofiber gel rich in double bonds; and to prepare a nanofiber hydrogel or aerogel material rich in double bonds by using the method for preparing a nanofiber gel rich in double bonds. The present invention achieves physical aggregation, overlapping and simultaneous surface modification of nanofibers during the gelation process by regulating the volatile reagents during the chemical vapor deposition process, and finally obtains a double-bond nanofiber gel with rich double bonds inside and esterified nanofiber surfaces. The method is simple to operate, easy to implement, and highly operable. The obtained nanofiber gel rich in double bonds has the potential for functionalization, which broadens its scope of application.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] According to one aspect of the present invention, a method for preparing a nanofiber hydrogel rich in double bonds is provided, characterized in that it comprises the following steps:

[0009] The double-bond-rich nanofiber hydrogel can be obtained by chemical vapor deposition method, using a reagent containing a volatile double-bond compound to perform double-bond modification treatment on an aqueous nanofiber dispersion; the volatile double-bond compound is an acyl chloride compound containing a double bond.

[0010] Furthermore, the reagent containing a volatile double bond compound also contains at least one of volatile acetic acid, hydrochloric acid, hydrofluoric acid, hydrobromic acid, hydroiodic acid, sulfurous acid, acetyl chloride, benzoyl chloride, and oxalyl chloride.

[0011] Furthermore, the reagent containing the volatile double bond compound also contains at least one of the volatile monomers of acrylic acid, methacrylic acid, styrene, butyl acrylate, and methyl methacrylate.

[0012] Furthermore, the double bond-containing acyl chloride compound is at least one of methacryloyl chloride, undecylenyl chloride, acryloyl chloride, crotonyl chloride, and vinylsulfonyl chloride.

[0013] Furthermore, the surface of the nanofiber is negatively charged, and is obtained by treating the fiber raw material with chemical treatment and / or mechanical treatment, wherein the mechanical treatment method is high-pressure homogenization treatment, ultrasonic crushing treatment, ultrafine grinding treatment, colloid milling treatment, microjet treatment, preferably high-pressure homogenization treatment; the chemical pretreatment method is chemical oxidation method, preferably TEMPO oxidation.

[0014] Furthermore, the nanofiber is derived from any one of nanocellulose, nanochitin and nanosilk.

[0015] Furthermore, the method for preparing a nanofiber hydrogel rich in double bonds is characterized in that the double bond modification treatment time is 0.5 to 24 hours, and the molar ratio of the double bond-containing acyl chloride compound to the nanofiber hydroxyl group is in the range of 1 to 200:1.

[0016] Furthermore, the concentration of the aqueous nanofiber dispersion is 0.1-1 wt %.

[0017] Furthermore, the method for preparing the double bond-rich nanofiber hydrogel is characterized in that the double bond content in the hydrogel is 1.0 to 100 mmol / g.

[0018] According to another aspect of the present invention, a nanofiber gel rich in double bonds is provided. The nanofiber gel rich in double bonds is prepared by a chemical vapor deposition method, and the nanofiber gel rich in double bonds has stable mechanical properties. The storage modulus of the gel prepared under different conditions can be 0.2×10 3 ~6.0×104 Pa.

[0019] According to another aspect of the present invention, a method for preparing a nanofiber aerogel rich in double bonds is provided, wherein the nanofiber aerogel rich in double bonds is prepared by freeze-drying the nanofiber aerogel rich in double bonds, and the double bond content of the nanofiber aerogel rich in double bonds is 0.1 to 4.0 mmol / g.

[0020] Furthermore, the double-bond-rich nanofiber hydrogel / aerogel prepared by the chemical vapor deposition method can obtain excellent hydrophobicity and fluorescence properties by functionalizing the double bonds through the thiol-ene click chemistry method. The modification reagent used in the thiol-ene click chemistry is a thiol compound, preferably cysteine, glutathione, octadecanethiol, 7-mercapto-4-methylcoumarin, 3-mercaptopropionic acid, etc., preferably at least one of octadecanethiol and 7-mercapto-4-methylcoumarin.

[0021] According to another aspect of the present invention, there is provided an application of a nanofiber gel rich in double bonds, such as the application of the nanofiber hydrogel rich in double bonds or the nanofiber aerogel rich in double bonds in the fields of sustained release, filtration, catalysis, thermal insulation, adsorption or sensor.

[0022] The beneficial effects of the present invention are:

[0023] (1) The present invention can directly use double-bond-containing acyl chloride compounds to treat aqueous nanofiber dispersions through chemical vapor deposition to prepare double-bond-rich nanofiber gels in one step. The preparation method is simple and efficient.

[0024] (2) The nanofiber gel rich in double bonds prepared by the present invention is rich in a large number of double bond compounds, and the surface of the nanofiber also has covalently connected double bonds, which can effectively solve the problem of single surface chemical properties of nanofiber gel prepared by physical methods, and provide convenience for the subsequent functionalization of hydrogels and aerogels. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 It is a polarized photo of a double-bond-rich nanofiber hydrogel prepared from different volatile acidic compounds and double-bond-containing acyl chloride compounds in the present invention;

[0027] Figure 2The viscoelastic performance diagram of the double-bond-rich nanofiber hydrogel prepared by different volatile acidic compounds and double-bond-containing acyl chloride compounds in the present invention and the mechanical performance analysis diagram of the hydrogel prepared by using acyl chloride compounds in different molar ratios;

[0028] Figure 3 It is an X-ray photoelectron spectroscopy (XPS) analysis diagram of the nanofiber gel rich in double bonds and the gel without double bonds prepared by the present invention;

[0029] Figure 4 It is the composition analysis diagram of each element on the surface of the nanofiber gel rich in double bonds and the gel without double bonds prepared by the present invention;

[0030] Figure 5 It is an optical photo and a field emission scanning electron fiber microscope analysis diagram of the double bond-rich nanofiber aerogel prepared by the present invention;

[0031] Figure 6 This is a fluorescence performance analysis diagram of the double bonds in the double bond-rich nanofiber aerogel prepared by the present invention after being modified by a mercapto-ene click reaction;

[0032] Figure 7 It is a water contact angle analysis diagram of the double bonds in the double bond-rich nanofiber aerogel prepared by the present invention after being modified by a thiol-ene click reaction. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings, technical process steps, specific implementation conditions and materials in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] According to an embodiment of the present invention, a method for preparing a nanofiber gel rich in double bonds by chemical vapor deposition and its preparation and application are provided.

[0035] According to one aspect of the present invention, a method for preparing a nanofiber hydrogel rich in double bonds is provided, characterized in that it comprises the following steps:

[0036] (1) preparing an aqueous nanofiber dispersion using a cellulose raw material;

[0037] (2) The aqueous nanofiber dispersion is subjected to a chemical vapor deposition treatment containing a volatile double bond compound to obtain a nanofiber hydrogel rich in double bonds; the volatile double bond compound is an acyl chloride compound containing double bonds.

[0038] In order to better understand the above technical solution, specific embodiments of the present invention are described in detail below.

[0039] Among them, the double-bond-rich nanofiber gel prepared by chemical vapor deposition provided by the present invention can flexibly adjust the quality of the gel according to factors such as the actual use environment, mold size, and test requirements. In the following examples, 4 g is used as the gel preparation standard to illustrate the present invention.

[0040] Embodiment 1

[0041] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride containing a molar ratio of 50:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a nanocellulose hydrogel rich in double bonds.

[0042] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration. The double bond content of the hydrogel before washing is 50mmol / g, and the double bond content of the hydrogel after washing is 5.4mmol / g; and the strength is characterized by viscoelasticity measurement, that is, 6.8×10 3 Pa.

[0043] The hydrogel is freeze-dried to obtain a nanocellulose aerogel rich in double bonds. The double bond content of the nanocellulose aerogel rich in double bonds is measured by saponification and bromination titration, which is 4.0 mmol / g.

[0044] Embodiment 2

[0045] Weigh 4 g of a uniform and transparent nanocellulose dispersion with a concentration of 0.5 wt %, remove bubbles from the dispersion by ultrasonic bath and load it into a mold, place methacrylic acid chloride and hydrochloric acid in a molar ratio of 50:1 to the hydroxyl group of the nanofibers in a sealed container to provide a gas environment for physical crosslinking, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 h to obtain a double bond-rich nanocellulose dispersion.

[0046] Nanocellulose hydrogel.

[0047] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for several times to ensure that the residual hydrochloric acid is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 46mmol / g, and the double bond content of the hydrogel after washing is 5.0mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 6.5×10 3 Pa.

[0048] The hydrogel is freeze-dried to obtain a nanocellulose aerogel rich in double bonds.

[0049] The reagent containing the volatile double bond compound used in the present invention is not limited to containing only acyl chloride but also contains at least one of volatile acetic acid, hydrochloric acid, hydrofluoric acid, hydrobromic acid, hydroiodic acid, sulfurous acid, acetyl chloride, benzoyl chloride and oxalyl chloride. The following Examples 3 and 4 add volatile acetic acid and acetyl chloride to illustrate the present invention based on Example 1.

[0050] Embodiment 3

[0051] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride and acetic acid in a molar ratio of 50:1 to the hydroxyl group of the nanofibers in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a nanocellulose hydrogel rich in double bonds.

[0052] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 50mmol / g, and the double bond content of the hydrogel after washing is 5.3mmol / g. Its strength is characterized by viscoelasticity measurement, that is, 6.2×10 3 Pa.

[0053] Embodiment 4

[0054] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride and acetyl chloride in a molar ratio of 50:1 to the hydroxyl groups of the nanofibers in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a nanocellulose hydrogel rich in double bonds.

[0055] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 55mmol / g, and the double bond content of the hydrogel after washing is 6.0mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 7.0×10 3 Pa.

[0056] The volatile double bond compound used in the chemical vapor deposition of the present invention is not limited to a single volatile double bond compound, and can be replaced by a double chemical vapor deposition of an acyl chloride compound containing a double bond or a volatile acid and a volatile double bond monomer. The volatile double bond monomer provided by the present invention is any one of acrylic acid, methacrylic acid, styrene, butyl acrylate or methyl methacrylate. The following Examples 5 and 6 are respectively described with butyl acrylate and methyl methacrylate.

[0057] Embodiment 5

[0058] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride and a certain amount of butyl acrylate solution in a molar ratio of 50:1 to the hydroxyl group of the nanofibers in a closed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a nanocellulose hydrogel rich in double bonds.

[0059] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 70mmol / g, and the double bond content of the hydrogel after washing is 7.5mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 5.3×10 3 Pa.

[0060] Embodiment 6

[0061] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place hydrochloric acid containing a molar ratio of 50:1 to the hydroxyl group of the nanofiber and a certain amount of methyl methacrylate solution in a sealed container to provide a gas environment in which physical crosslinking can occur, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a nanocellulose hydrogel rich in double bonds.

[0062] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 46mmol / g, and the double bond content of the hydrogel after washing is 7.0mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 5.5×10 3 Pa.

[0063] The double bond-containing acyl chloride compound used in the present invention is not limited to methacryloyl chloride. Methacryloyl chloride can be replaced by any one of undecenoyl chloride, acryloyl chloride, crotonoyl chloride or vinylsulfonyl chloride. The present invention is illustrated by undecenoyl chloride in the following Example 7.

[0064] Embodiment 7

[0065] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place undecylenic acid chloride containing a molar ratio of 50:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a nanocellulose hydrogel rich in double bonds.

[0066] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 50mmol / g, and the double bond content of the hydrogel after washing is 4.2mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 1.6×10 3 Pa.

[0067] The source of the nanofibers used in the present invention is not limited to nanocellulose, and can be replaced by chitin nanofibers or silk nanofibers. The following examples 8 and 9 illustrate the present invention using chitin nanofibers and silk nanofibers.

[0068] Embodiment 8

[0069] Weigh 4 g of a uniform, transparent chitin nanofiber dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride containing a molar ratio of 50:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a chitin nanofiber hydrogel rich in double bonds.

[0070] The chitin nanofiber hydrogel after the reaction can also be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the chitin nanofiber hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 53 mmol / g, and the double bond content of the hydrogel after washing is 5.3 mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 5.5 × 10 3 Pa.

[0071] Embodiment 9

[0072] Weigh 4 g of a uniform, transparent silk nanofiber dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride containing methyl methacryloyl chloride in a molar ratio of 50:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a silk nanofiber hydrogel rich in double bonds.

[0073] The silk nanofiber hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the silk nanofiber hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 55mmol / g, and the double bond content of the hydrogel after washing is 5.2mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 0.2×10 3 Pa.

[0074] The reaction time for preparing the double bond-rich nanofiber hydrogel by chemical vapor deposition of the present invention is not limited to 2 hours, and any time from 0.5 to 24 hours can be used instead of 2 hours; the molar ratio of acyl chloride to the surface hydroxyl group of the nanofiber is not limited to 50:1, and any ratio from 1 to 200:1 can be used instead of 50:1. The following Examples 10 and 11 illustrate the present invention with different reaction times and molar equivalents of acyl chloride.

[0075] Embodiment 10

[0076] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride containing a molar ratio of 1:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 24 hours to obtain a nanocellulose hydrogel rich in double bonds.

[0077] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 10mmol / g, and the double bond content of the hydrogel after washing is 2.8mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 2.3×10 3 Pa.

[0078] Embodiment 11

[0079] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride containing a molar ratio of 200:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 0.5 h to obtain a nanocellulose hydrogel rich in double bonds.

[0080] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 55mmol / g, and the double bond content of the hydrogel after washing is 10.2mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 8.0×10 3 Pa.

[0081] The concentration of the nanofiber dispersion used in the present invention is not limited to 0.5 wt %, and any value between 0.1 and 1 wt % may be used instead of 0.5 wt %. The present invention is described in the following examples 12 and 13 using different nanofiber dispersion concentrations.

[0082] Embodiment 12

[0083] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.1 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride containing methyl methacrylate in a molar ratio of 50:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 0.5 h to obtain a nanocellulose hydrogel rich in double bonds.

[0084] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 20mmol / g, and the double bond content of the hydrogel after washing is 2.6mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 0.3×10 3 Pa.

[0085] Embodiment 13

[0086] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 1 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place methacryloyl chloride containing a molar ratio of 50:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment for physical crosslinking and chemical modification, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 0.5 h to obtain a nanocellulose hydrogel rich in double bonds.

[0087] The nanocellulose hydrogel after the reaction can be washed with ethanol and distilled water for many times to ensure that the organic acid containing double bonds inside is washed away, and the final nanocellulose hydrogel with rich double bonds on the surface is obtained. The double bond content of the nanocellulose hydrogel rich in double bonds is measured by saponification bromination titration method, that is, the double bond content of the hydrogel before washing is 50mmol / g, and the double bond content of the hydrogel after washing is 7.5mmol / g; and its strength is characterized by viscoelasticity measurement, that is, 1.0×10 4 Pa.

[0088] On the basis of the nanofiber gel rich in double bonds prepared by the chemical vapor deposition method provided by the present invention, the nanofiber hydrogel / aerogel rich in double bonds is functionalized by a thiol-ene click reaction. The functional thiol compounds capable of click reaction include cysteine, glutathione, octadecanethiol, 7-mercapto-4-methylcoumarin, 3-mercaptopropionic acid, etc., preferably octadecanethiol and 7-mercapto-4-methylcoumarin. In the following Examples 14 and 15, the present invention is illustrated by the thiol-ene click reaction of octadecanethiol and 7-mercapto-4-methylcoumarin.

[0089] Embodiment 14

[0090] Based on Example 1, this example uses the thiol-ene click reaction of octadecyl mercaptan to functionalize the nanocellulose gel rich in double bonds. At the same time, the hydrogel without double bonds in Comparative Example 1 is used for comparative experiments to verify the influence of double bonds on its subsequent functionalization.

[0091] The nanocellulose gel rich in double bonds was immersed in a 50 mL dichloromethane solution containing 1 g of octadecyl mercaptan and 0.5 g of 2,2-dimethoxy-2-acetophenone. The reaction system was sealed and irradiated under a UV lamp (6W, 365 nm) for 0.5 h. After reacting for 15 min, the gel after the reaction was taken out and washed with ethanol several times to remove the residual reactants, and then nitrogen was purged to remove the residual dichloromethane and ethanol on the surface. The water contact angle test of the nanocellulose gel rich in double bonds modified by octadecyl mercaptan was performed to characterize its hydrophobicity.

[0092] Embodiment 15

[0093] Based on Example 1, this example uses the thiol-ene click reaction of 7-mercapto-4-methylcoumarin to functionalize the nanocellulose gel rich in double bonds. At the same time, the hydrogel without double bonds in Comparative Example 1 is used for comparative experiments to verify the influence of the double bonds on its subsequent functionalization.

[0094] The double bond-rich nanocellulose gel was immersed in a mixture of N, N-dimethylformamide containing 10 mM 7-mercapto-4-methylcoumarin, with dimethylaminopyridine as a catalyst. After 15 minutes in the dark, the gel was taken out and washed repeatedly three times with pure N, N-dimethylformamide solution. The fluorescence properties of the double bond-rich nanocellulose hydrogel modified with 7-mercapto-4-methylcoumarin were characterized by fluorescence spectrophotometer test.

[0095] The nanofibers described in the above embodiments are prepared by TEMPO / NaBr / NaClO chemical oxidation method and high-pressure homogenization treatment, but the nanofibers used in the present invention are not limited to those prepared by this method. Nanofibers prepared by chemical oxidation method (such as TEMPO / NaBr / NaClO oxidation, TEMPO / laccase / O2 oxidation) and / or mechanical treatment method (high-pressure homogenization treatment, ultrasonic crushing treatment, ultrafine grinding treatment, colloid milling treatment, microjet treatment) are all within the scope of the present invention.

[0096] The embodiments involved in the present invention are not limited to the above embodiments. Table 1 briefly lists the preparation method, double bond content and mechanical properties of the double bond-rich nanofiber gel involved in the present invention, wherein the specific experimental process is the same as that of Example 1.

[0097] Table 1

[0098]

[0099]

[0100] Comparative Example 1

[0101] Weigh 4 g of a uniform, transparent nanocellulose dispersion with a concentration of 0.5 wt%, remove bubbles from the dispersion by water bath ultrasound and load it into a mold, place hydrochloric acid containing a molar ratio of 50:1 to the hydroxyl group of the nanofiber in a sealed container to provide a gas environment in which physical crosslinking can occur, place the dispersion in a chemical vapor deposition environment, and react at room temperature for 2 hours to obtain a nanocellulose hydrogel without double bonds.

[0102] The cellulose nanofiber hydrogel after the reaction was washed with ethanol and distilled water several times to ensure that the residual hydrochloric acid was washed away, and the final nanocellulose hydrogel was obtained. The viscoelasticity of the nanocellulose hydrogel was measured to characterize its strength, which was 2.3×10 3 Pa.

[0103] The hydrogel is freeze-dried to obtain a nanocellulose aerogel without double bonds.

[0104] Legend analysis:

[0105] Figure 1 Polarized photos of nanofiber hydrogels prepared by chemical vapor deposition of different volatile acidic compounds and double-bond acyl chloride compounds in Example 1, Example 7 and Comparative Example 1 (a, nanocellulose hydrogel prepared by hydrochloric acid chemical vapor deposition; b, nanocellulose hydrogel rich in double bonds prepared by methacryloyl chloride chemical vapor deposition; c, nanocellulose hydrogel rich in double bonds prepared by undecylenyl chloride chemical vapor deposition). Figure 1 It can be seen that the nanocellulose gels prepared by chemical vapor deposition of different volatile acyl chlorides and acidic compounds have high transparency and show obvious birefringence under polarized light. Figure 1 b and c show that the introduction of double bonds does not destroy the transparency and birefringence properties of the nanofiber hydrogel itself.

[0106] Figure 2 The viscoelastic properties of nanofiber hydrogels prepared by chemical vapor deposition of different volatile acidic compounds and double-bond acyl chloride compounds in Example 1, Example 7 and Comparative Example 1 and the mechanical properties analysis of hydrogels prepared by using different molar ratios of acyl chloride compounds in Example 10 and Example 11 are shown. Figure 2It can be seen that chemical vapor deposition of different volatile acidic compounds and double-bond acyl chloride compounds can prepare nanofiber gel materials with stable network structure. Among them, the storage modulus of the gel prepared by volatile hydrochloric acid chemical vapor deposition method is 2.3×10 3 Pa. The nanofiber gel prepared by methacrylic acid chloride chemical vapor deposition has the highest storage modulus, which can reach 6.8×10 3 Pa. It shows that the mechanical properties of the double bond-rich hydrogel prepared by the present invention are significantly better than those of the hydrogel prepared by the hydrochloric acid method; this is because the hydrolysis of the acyl chloride in the process of the present invention not only produces hydrochloric acid, but also introduces organic acid. The simultaneous action of the two acids is more conducive to the improvement of its mechanical properties. Undecylenic acid chloride has a long alkyl chain and its reaction activity is lower than that of methacrylic acid chloride, resulting in a storage modulus of only 1.6×10 3 Pa. This shows that the introduction of volatile double-bond-rich acyl chlorides during chemical vapor deposition can not only prepare stable hydrogel materials, but also enhance their mechanical properties. Figure 2 b It can be seen that under the conditions of the same nanofiber dispersion concentration and chemical vapor deposition time, within a certain range, the storage modulus of the double-bond-rich nanofiber hydrogel increases with the increase in the amount of acyl chloride compound; when the molar ratio of acyl chloride compound to nanofiber hydroxyl group exceeds 50:1, the storage modulus of the double-bond-rich nanofiber hydrogel tends to be stable.

[0107] Figure 3 and Figure 4 The X-ray photoelectron spectroscopy (XPS) analysis diagram of the acidic compounds and the gel containing double-bond acyl chloride compounds in the nanofiber gel prepared by chemical vapor deposition in Example 1 and Example 2 of the present invention and the composition table of each element on the gel surface determined therefrom (a, X-ray photoelectron spectroscopy analysis diagram of nanocellulose aerogel prepared by hydrochloric acid chemical vapor deposition; b, X-ray photoelectron spectroscopy analysis diagram of nanocellulose aerogel rich in double bonds prepared by methacryloyl chloride chemical vapor deposition). Figure 3 and Figure 4 It can be seen that due to the reaction between the acyl chloride and the hydroxyl groups on the surface of the nanofibers, the hydroxyl groups are consumed, and the COC / COH at 286.50eV is reduced from 66.22% to 50%. With the introduction of double bonds, CC / CH at 284.80eV is greatly increased from 7.91% to 22.23%. Furthermore, since the O / C of the grafted part of methacryloyl chloride on the surface of the nanofibers is only 0.33, which is much lower than the O / C of the nanofibers, the O / C of the surface of the modified nanofibers is reduced from 0.66 to 0.53. Therefore, it is proved that the esterification of the nanofiber surface introduces covalently linked double bonds; the nanofiber aerogel with rich double bonds on the surface can be successfully prepared by the chemical vapor deposition method provided by the present invention.

[0108] Figure 5 The optical photograph and field emission scanning electron microscopy analysis diagram of the double bond-rich nanofiber aerogel prepared by chemical vapor deposition in Example 13 of the present invention (a, optical photograph of the double bond-rich nanofiber aerogel; b, field emission scanning electron microscopy analysis diagram of the double bond-rich nanofiber aerogel). Figure 5 It can be seen from a that the double-bond-rich nanofiber aerogel prepared by chemical vapor deposition has a stable three-dimensional network structure that does not collapse. Figure 5 From the microscopic morphology of b, it can be seen that the aerogel network structure prepared by chemical vapor deposition of acyl chloride presents a uniform network structure, which further illustrates that the nanofiber gel prepared by chemical vapor deposition has an excellent nanofiber network structure.

[0109] Figure 6 The fluorescence performance analysis diagram of the double bond-rich nanofiber gel prepared by chemical vapor deposition in Example 14 of the present invention after the thiol-ene click reaction of the double bonds (a, fluorescence spectrum of the gel prepared by chemical vapor deposition of hydrochloric acid and methacryloyl chloride before and after the click reaction; b, optical photos of the gel prepared by chemical vapor deposition of hydrochloric acid and methacryloyl chloride before and after the click reaction under 365nm ultraviolet light). Figure 6 As shown in a and b, the 7-mercapto-4-methylcoumarin, which has fluorescence properties, reacts with the double bonds in the nanofiber gel through a thiol-ene click reaction. After the reaction, the nanofiber gel exhibits an obvious fluorescence enhancement effect. Compared with the nanofiber gel prepared by direct hydrochloric acid chemical vapor deposition without double bonds, its fluorescence intensity is enhanced by 3 times. It is further explained that the nanofiber gel rich in double bonds provided by the present invention can further realize fluorescence functionalization due to the presence of abundant double bond functional groups, thereby broadening its application field.

[0110] Figure 7 The water contact angle analysis diagram of the double bond-rich nanofiber gel prepared by chemical vapor deposition in Example 13 of the present invention after the thiol-ene click reaction of the double bonds (a, water contact angle diagram of the gel prepared by chemical vapor deposition of hydrochloric acid and methacryloyl chloride before and after the click reaction; b, hydrophobic photo of the gel prepared by chemical vapor deposition of hydrochloric acid and methacryloyl chloride after the click reaction). Figure 7 a Water contact angle analysis shows that after the introduction of hydrophobic octadecyl mercaptan by thiol-ene click reaction on the nanofiber hydrogel prepared by chemical vapor deposition of hydrochloric acid and methacryloyl chloride, its water contact angle increased from 13.10° and 10.76° to 21.51° and 46.00° respectively. Then, the hydrophobic click reaction of octadecyl mercaptan on the nanofiber aerogel prepared by chemical vapor deposition of hydrochloric acid and methacryloyl chloride was also carried out. After the reaction, the hydrophobicity of the aerogel containing double bonds was greatly increased, and the water contact angle was 102.97°. Figure 7The hydrophobic photo in b further verifies the hydrophobic enhancement effect of the double bond-rich aerogel. The aqueous solution droplets on the surface of the double bond-containing aerogel are relatively complete spheres, while the aerogel without double bonds collapses rapidly due to water absorption. The introduction of double bonds greatly improves the functionalization potential of the nanofiber gel.

Claims

1. A method for preparing a nanofiber hydrogel rich in double bonds, characterized in that: The following steps are involved: (1) preparing an aqueous nanofiber dispersion using a cellulose raw material; (2) subjecting the aqueous nanofiber dispersion to chemical vapor deposition of a volatile double-bond compound to obtain a nanofiber hydrogel rich in double bonds; The nanofibers are sourced from nanocellulose, chitin nanofibers, and silk nanofibers; the volatile double-bond compound is at least one of methacryloyl chloride, undecylenyl chloride, acryloyl chloride, crotonyl chloride, and vinylsulfonyl chloride.

2. The method for preparing a double bond-rich nanofiber hydrogel according to claim 1, characterized in that: The reagent containing the volatile double bond compound also contains at least one of volatile acetic acid, hydrochloric acid, hydrofluoric acid, hydrobromic acid, hydroiodic acid, sulfurous acid, acetyl chloride, benzoyl chloride and oxalyl chloride.

3. The method for preparing a double bond-rich nanofiber hydrogel according to claim 1, characterized in that: The reagent containing the volatile double-bond compound also contains at least one of the volatile monomers acrylic acid, methacrylic acid, styrene, butyl acrylate and methyl methacrylate.

4. The method for preparing a double bond-rich nanofiber hydrogel according to any one of claims 1 to 3, characterized in that: The double bond modification treatment time is 0.5 to 24 hours, and the molar ratio of the double bond-containing acyl chloride compound to the nanofiber hydroxyl group is in the range of 1 to 200:

1.

5. The method for preparing a double bond-rich nanofiber hydrogel according to claim 1, characterized in that: The double bond content in the hydrogel is 1.0 to 100 mmol / g.

6. A nanofiber hydrogel rich in double bonds, characterized in that: The nanofiber hydrogel rich in double bonds is prepared by the preparation method of any one of claims 1 to 5, and the nanofiber hydrogel rich in double bonds has stable mechanical properties. The storage modulus of the gel prepared under different conditions is 0.2×10 3 ~6.0×10 4 Pa.

7. A nanofiber aerogel rich in double bonds, characterized in that: The double bond-rich nanofiber hydrogel according to claim 6 is prepared by freeze-drying, and the double bond content of the double bond-rich nanofiber aerogel is 0.1-4.0 mmol / g.

8. Application of nanofiber hydrogel or aerogel rich in double bonds, characterized in that: Application of the double bond-rich nanofiber hydrogel as claimed in claim 6 or the double bond-rich nanofiber aerogel as claimed in claim 7 in the fields of sustained release, filtration, catalysis, thermal insulation, adsorption or sensor.

Citation Information

Patent Citations

  • Preparation method of cellulose nanofiber biomass gel and aerogel

    CN106893116A

  • Cellulose base graft modification reversible gel and preparation method thereof

    CN110408050A